2020
DOI: 10.1212/wnl.0000000000008684
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal optic neuritis-unrelated visual evoked potential changes in NMO spectrum disorders

Abstract: ObjectiveTo investigate if patients with neuromyelitis optica spectrum disorder (NMOSD) develop subclinical visual pathway impairment independent of acute attacks.MethodsA total of 548 longitudinally assessed full-field visual evoked potentials (VEP) of 167 patients with NMOSD from 16 centers were retrospectively evaluated for changes of P100 latencies and P100-N140 amplitudes. Rates of change in latencies (RCL) and amplitudes (RCA) over time were analyzed for each individual eye using linear regression and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…As shown in other studies, no significant differences in latency or amplitude of the P100 component were found based on AQP4 serostatus (Watanabe et al, 2009;Ringelstein et al, 2014Ringelstein et al, , 2020. However, we noted a significantly higher prevalence of the absence of response in at least one eye in patients with NMOSD who were AQP4[+] (44%) vs. AQP4[-] (4%).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…As shown in other studies, no significant differences in latency or amplitude of the P100 component were found based on AQP4 serostatus (Watanabe et al, 2009;Ringelstein et al, 2014Ringelstein et al, , 2020. However, we noted a significantly higher prevalence of the absence of response in at least one eye in patients with NMOSD who were AQP4[+] (44%) vs. AQP4[-] (4%).…”
Section: Discussionsupporting
confidence: 71%
“…The logistic regression model revealed a significant association between AQP4-positive status and a higher rate of absentVEP responses, but no such relationship was found for the rate of abnormal responses. Notably, in a recent longitudinal study by Ringelstein et al, NMOSD patients with no history of ON showed a progressive delay in latency, which was not attributed to serostatus (Ringelstein et al, 2020). In view of this, we suggest that AQP4-positive status results in a worse outcome in VEP responses, which is mainly expressed in patients with severe impairment of the optic nerve.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Occasionally, studies have reported neuroaxonal damage also in eyes without prior ON in AQP4-IgG-seropositive NMOSD, which could be interpreted as evidence as such. 39 However, earlier studies had cohort heterogeneity due to incomplete antibody characterization or inclusion of patients with antibody-negative NMOSD. Furthermore, ON in NMOSD often occurs near the chiasm, and neuroaxonal damage can be caused by chiasmal crossover from an affected eye to the fellow eye, 40 which might not be clinically apparent.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Accrual of severe disability in NMOSD appears to be driven primarily by irreversible attack-related injury, although emerging evidence suggests that subclinical disease processes may be present. [5][6][7][8] Immunosuppression is typically used in NMOSD to reduce the risk of attacks. There are limited data on the effect of drugs used empirically in NMOSD on disability.…”
Section: Classification Of Evidencementioning
confidence: 99%